Recent Advances in Photoluminescence Detection of Fingerprints - E. Roland Menzel (The Scientific World Journal)
Photoluminescence detection of latent fingerprints has over the last quarter century brought about a new level of fingerprint detection sensitivity. The current state of the art is briefly reviewed to set the stage for upcoming new fingerprint processing strategies. These are designed for suppression of background fluorescence from articles holding latent prints, an often serious problem. The suppression of the background involves time-resolved imaging, which is dealt with from the perspective of instrumentation as well as the design of fingerprint treatment strategies. These focus on lanthanide chelates, nanocrystals, and nanocomposites functionalized to label fingerprints.